Paramedic Disaster Health Management Competencies: A Scoping Review. Issue 3 (28th May 2019) - Horrocks, Peter; Hobbs, Lisa; Tippett, Vivienne; Aitken, Peter
Abstract: Introduction: Paramedics are tasked with providing 24/7 prehospital emergency care to the community. As part of this role, they are also responsible for providing emergency care in the event of a major incident or disaster. They play a major role in the response stage of such events, both domestic and international. Despite this, specific standardized training in disaster management appears to be variable and inconsistent throughout the profession. A suggested method of building disaster response capacities is through competency-based education (CBE). Core competencies can provide the fundamental basis of collective learning and help ensure consistent application and translation of knowledge into practice. These competencies are often organized into domains, or categories of learning outcomes, as defined by Blooms taxonomy of learning domains. It is these domains of competency, as they relate to paramedic disaster response, that are the subject of this review. Methods: The methodology for this paper to identify existing paramedic disaster response competency domains was adapted from the guidance for the development of systematic scoping reviews, using a methodology developed by members of the Joanna Briggs Institute (JBI; Adelaide, South Australia) and members of five Joanna Briggs Collaborating Centres. Results: The literature search identified six articles for review that reported on paramedic disaster response competency domains. The results were divided into two groups: (1) General Core Competency Domains, which are suitable for all paramedics (both Advanced Life Support [ALS] and Basic Life Support [BLS]) who respond to any disaster or major incident; and (2) Specialist Core Competencies, which are deemed necessary competencies to enable a response to certain types of disaster. Further review then showed that three separate and discrete types of competency domains exits in the literature: (1) Core Competencies, (2) Technical/Clinical Competencies, and (3) Specialist Technical/Clinical Competencies. Conclusions: The most common domains of core competencies for paramedic first responders to manage major incidents and disasters described in the literature were identified. If it's accepted that training paramedics in disaster response is an essential part of preparedness within the disaster management cycle, then by including these competency domains into the curriculum development of localized disaster training programs, it will better prepare the paramedic workforce's competence and ability to effectively respond to disasters and major incidents.